FACTOR BISEMIRINGS - Hussain, Fawad (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper we define congruence relations on bisemirings and bisemiring homomorphisms. We show that each bisemiring homomorphism defines a congruence relation on a bisemiring and then we introduce factor bisemirings. In the last section, we prove analogue of the isomorphism theorems.